Association of chronic periodontitis with prostatic hyperplasia and prostatitis: A population‐based cohort study in Taiwan. Issue 1 (22nd August 2020) - Fu, Earl; Cheng, Chia‐Mao; Chung, Chi‐Hsiang; Lee, Wei‐Cheng; Chen, Wei‐Liang; Sun, Guang‐Huan; Chien, Wu‐Chien
Abstract: Background: Association between periodontitis and prostate diseases of benign prostatic hyperplasia (BPH) and prostatitis is uncertain. Methods: From the National Health Insurance Research Database of Taiwan, 5, 510 patients with newly diagnosed chronic periodontitis and participated in therapies were selected from 2000 to 2015 as cohort 1. Matched with age and index year, 5, 510 patients with periodontitis diagnosis without therapy were selected as cohort 2, and 5, 510 participants without diagnosis were used as control. Cox proportional hazard and survival analysis were performed to compare the risks and the survival probabilities among cohorts. Results: In two periodontitis cohorts, 636 and 638 participants compared with 550 in control (1, 174 and 1, 187 versus 989 per 100, 000 person‐years) had prostate disorder. Difference was identified for prostatitis (n = 68, 70 versus 34; rate = 125, 130 versus 61 /100, 000 person‐years; P <0.001) but not for BPH (n = 577, 575, versus 529; rate = 1, 065, 1, 070 versus 951 /100, 000 person‐years, respectively). Different survival probabilities for prostate disorder and prostatitis, but not for BPH, were observed among cohorts. Periodontitis patients were more likely to develop prostate disorder after adjustment (adjusted hazard ratio [aHR] of 2.590 to 2.641 by competing model). With stratification, risks between two periodontitis cohorts exhibited no difference. When BPH cases were excluded, the aHRs for prostatitis were 4.611 to 4.798. Conclusions: Despite treatment, the patients with periodontitis had higher risk of developing prostatitis than patients without periodontitis.